UPAYA MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA PADA MATERI BANGUN DATAR SEGITIGA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) - Indra Jaya (State Islamic University of North Sumatra, 2017)
This study aims to determine the mathematical communication skills of students before and after the application of PBL learning on the subject of a triangle in class VII MTs. Islamiyah and improvement of students' mathematical communication skills through the application of PBL learning on the subject of triangular in class VII MTs. Islamiyah Medan. The type of this research is Classroom Action Research which consists of two cycles. The subjects of the study were students of class VII MTs. Islamiyah Medan as many as 28 people. The instruments of data collection used are tests (in essay form), interviews, and observations. Data analysis techniques performed include: data reduction, data analysis, data interpretation, and conclusions. The findings in this study show: (1) the students' mathematical communication skills before the application of PBL learning on the subject of a triangular in class VII MTs. Islamiyah scored an average of 47.43 (2) Improvement of mathematical communication in cycle I was obtained 15 students (53,57%) who have medium minimum mathematical communication capability and cycle II obtained 23 students (82,14%) who have high mathematical communication (3) The ability of students' mathematical communication after the application of PBL learning on the subject of a triangular in class VII MTs. Islamiyah on the action of class I cycle gets an average score of 64.68 and after doing action in cycle II is 75,3. Based on research results, it can be concluded that by applying the Problem Based Learning (PBL) model of learning can improve students' mathematical communication abilities on the subject of triangular in class VII MTs. Islamiyah.